Java Regular Expressions: Taming the java.util.regex Engine - Habibi, Mehran (Apress, 2012)
This book is a comprehensive introduction to the regular expression support built into J2SE, and it's designed to help Java programmers who have little to no experience with regular expressions. It's meant to be both a reference and an explanatory text. Although a background in regular expressions is helpful, I don't make any such assumptions when presenting the material. The central aim is to help everyday programmers solve everyday problems.